Dalla parte dei bambini. Considerazioni sull’approccio diagnostico e terapeutico nei “disturbi” dello sviluppo - Bembina, Adriana; Della Putta, Daniela (Il sogno della farfalla, 2013)
Starting from a comparative analysis of the most widespread theories on the psychopathology of development, the authors discuss the existing ideas on the child and the characteristics of his development, exploring the subsequent consequences on the nosographic classification and treatment of pathological anomalies. In this, M. Fagioli’s Birth Theory (1972) proposes an innovative view of a child’s human reality and thus seems to permit a better diagnostic and therapeutic practice. Two clinical cases concerning DCD (Developmental Coordination Disorder) and “developmental delay” proposed in this article, aim to outline the diagnostic and therapeutic repercussions stemming from the idea of a child whose human identity does exist from the beginning but must develop in the relationship with another person. The authors try to show that, as a non-conscious mental reality prevails in the newborn and child, an approach based exclusively on a conscious-rational method will prove to be inappropriate both in observing and intervening on a human condition that escapes from its control.